2005
DOI: 10.2307/3588527
|View full text |Cite
|
Sign up to set email alerts
|

Making the Invisible Visible: A Responsive Evaluation Study of ESL and Spanish Language Services for Immigrants in a Small Rural County in Indiana

Abstract: This article describes a responsive evaluation study of ESL services and Spanish language services for immigrants in a rural county in Indiana. An ESL specialist led the evaluation of language services in the county from the perspectives of language providers and recipients. The responsive evaluation-a form of action research that uses stakeholders' issues and concerns as bases for evaluating a program and a plan for improvements-identified the services and resources available to new residents in the community… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 8 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…As “trusted leaders,” educators and other institutional leaders can enhance local perceptions of immigrants by highlighting their contributions (Fennelly and Federico 2008:177) and dispelling native‐born residents' misconceptions. They can also serve as brokers for educational and social services, enhance immigrant understandings of local culture and institutions (e.g., the school system), facilitate immigrants' entrée to community events, and provide access to English‐language instruction (Pawan and Thomalla 2005). The latter is especially important for enhancing community acceptance and economic integration and mobility (Chiswick and Miller 2002; Gonzalez 2000; McHugh, Gelatt, and Fix 2007; Parra and Pfeffer 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As “trusted leaders,” educators and other institutional leaders can enhance local perceptions of immigrants by highlighting their contributions (Fennelly and Federico 2008:177) and dispelling native‐born residents' misconceptions. They can also serve as brokers for educational and social services, enhance immigrant understandings of local culture and institutions (e.g., the school system), facilitate immigrants' entrée to community events, and provide access to English‐language instruction (Pawan and Thomalla 2005). The latter is especially important for enhancing community acceptance and economic integration and mobility (Chiswick and Miller 2002; Gonzalez 2000; McHugh, Gelatt, and Fix 2007; Parra and Pfeffer 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, according to a few participants, institutions mandated to provide bilingual interpreters sometimes failed to do so (see Marrow 2005:791; Pawan and Thomalla 2005). One participant attributed the ability to bypass mandated services to the rural setting:…”
mentioning
confidence: 99%
“…As noted by Pawan and Thomalia (2005), private sector ESL programs can be met with strong skepticism on the part of the Latin American communities they target, seeming to be more focused on improving human capital and profits for the company providing them, rather than for the community involved. English-speaking immigrant workers are also subject to exploitation, being used by companies as all-purpose translators without additional benefits.…”
Section: Moving Forward: How and Where This Model Can Workmentioning
confidence: 95%
“…In order to provide a glimpse into how the government's policies and practices around language status and acquisition affect a portion of Indiana's Spanish-speaking population, evidence will be cited from a recent study of ESL and language services in one rural Indiana county (Pawan & Thomalla, 2005). While the overall population of this county is rather small, at 14,000, and the Latino portion is only about 1%, planning for language is still an important task for many in business, education, and local government.…”
Section: Implications Of State-level Language Policies and Practices mentioning
confidence: 99%
“…While the overall population of this county is rather small, at 14,000, and the Latino portion is only about 1%, planning for language is still an important task for many in business, education, and local government. In their research of the kinds of language services that were being offered to the Latino immigrant community, Pawan & Thomalla (2005) found that many services were quite scattered and showed little evidence of any planning. For example, interpretation services for Spanish speakers in hospitals, courts, and even schools were often provided only on an ad-hoc basis by untrained bilingual staff or volunteers.…”
Section: Implications Of State-level Language Policies and Practices mentioning
confidence: 99%